New method for establishing intercalibration intervals of measuring instruments based on the study of metrological reliability - Masharipov Shodlik M.; Rakhmatullaev Sarvar A.; Djumaniyazova Nigina A. (E3S Web of Conferences)
This paper introduces a novel method for establishing intercalibration intervals of measuring instruments used for physical and chemical quantities. The approach involves increasing intermediate checks and monitoring metrological properties to determine intercalibration intervals. It emphasizes the importance of ensuring metrological suitability before measurements and addresses the need to eliminate instrumental errors through adjustment or repair. The study analyzes progressive error changes in instruments, primarily due to mechanical wear and displacement of sensing elements. It discusses the process of determining and applying corrections to exclude instrumental and methodical errors, highlighting the importance of calibration and calculation methods. The research explores metrological reliability and its significance in establishing intercalibration intervals, presenting experimental results from a 25-day observation period. It delves into statistical aspects of failure rates and probability of failure-free operation for measuring instruments, introducing formulas for calculating these parameters. Additionally, the study examines the use of Shewhart control charts in process control and their application in observing changes in measurement uncertainty under precision conditions. It provides a formula for determining intercalibration intervals based on the probability of metrological failure and offers guidelines for adjusting these intervals during instrument operation.